Multiple contrast type tests for the evaluation of animal carcinogenicity studies. Issue 1 (2nd January 2017) - Rahman, Mohammad; Tiwari, Ram
ABSTRACT: The Cochran–Armitage (CA) test is frequently used for testing the dose–response relationship in tumor incidence. This test is based on a weighted linear regression of proportions. It is well known that the CA test lacks power for nonlinear tumor outcomes. For general shape of outcomes, Hothorn and Bretz (2000) proposed a multiple contrast (MC) test. This test suggests the use of the maximum over several single contrasts, where each of them is chosen appropriately to cover a specific dose–response shape. In this work, two new test procedures are proposed and they are compared to the CA and MC tests using power.